2009
DOI: 10.1111/j.1742-1241.2009.02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin therapy and hypoglycaemia in Muslim type 2 diabetes patients during Ramadan

Abstract: Appropriate treatment adjustments can lead to improved diabetes management during Ramadan, with avoidance of significant weight gain and improved glucose control without hypoglycaemia. The addition of vildagliptin to metformin therapy during Ramadan in Muslim patients with type 2 diabetes was associated with a reduction in the incidence of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 12 publications
9
76
1
4
Order By: Relevance
“…Furthermore, because of the MTD requirement, for patients randomized to sulphonylurea, the pre‐trial sulphonylurea was to be kept stable until Ramadan. The dose of sulphonylureas in this trial was, however, consistent with or higher than doses used in other Ramadan trials, as well as in clinical practice 9, 10, 11, 31, 32, 33, 34. Generally, for sulphonylureas administered at higher than half the maximum approved dose, the glucose‐lowering effect levels off as the dose increases 35.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, because of the MTD requirement, for patients randomized to sulphonylurea, the pre‐trial sulphonylurea was to be kept stable until Ramadan. The dose of sulphonylureas in this trial was, however, consistent with or higher than doses used in other Ramadan trials, as well as in clinical practice 9, 10, 11, 31, 32, 33, 34. Generally, for sulphonylureas administered at higher than half the maximum approved dose, the glucose‐lowering effect levels off as the dose increases 35.…”
Section: Discussionsupporting
confidence: 80%
“…A real-world observational and non-interventional study, VECTOR, conducted in United Kingdom Muslim patients with type 2 diabetes mellitus fasting during Ramadan demonstrated no hypoglycemic events (HEs) and better glycemic control with vildagliptin compared with gliclazide [11] . In a similar study by Devendra et al [12] conducted in North West London, both vildagliptin and gliclazide were associated with similar reductions in mean glycosylated haemoglobin A1c (HbA1c).…”
Section: Introductionmentioning
confidence: 81%
“…A number of observational studies have examined the efficacy and safety of DPP-4 inhibitor treatment during Ramadan [32,[43][44][45][46]. In the VECTOR study, no self-reported hypoglycaemic events were reported in the vildagliptin group compared with 35 events in 15 patients (41.7%) in the gliclazide arm (including one severe event).…”
Section: Dipeptidyl Peptidase-4 (Dpp-4) Inhibitorsmentioning
confidence: 99%